Analisis Tingkat Pengetahuan Swamedikasi Siswa SMA Negeri 12 Makassar: ANALYSIS OF SELF-MEDICATION KNOWLEDGE LEVEL OF SMA NEGERI 12 MAKASSAR STUDENTS - Aini, Azizah Nur; Jangga; Siti Nurul Haliza (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2025)
Self-medication is an act of treatment to overcome minor complaints with drugs independently without a doctor's prescription. Proper self-medication can be done with sufficient knowledge. Meanwhile, lack of knowledge can lead to unexpected impacts. The purpose of this study was to determine the level of knowledge of self-medication of SMA Negeri 12 Makassar students. This type of research is descriptive quantitative using stratified random sampling technique. Determination of the number of samples was carried out using the slovin formula involving 10th, 11th and 12th grade students of SMA Negeri 12 Makassar. The research was conducted in March 2025. The results of the study from 93 students revealed that 78.49% of SMA Negeri 12 Makassar students used analgesics and antipyretics. Mild complaints are the reason for the majority of self-medication (78.49%). The results of the students' knowledge level were 58.1% with poor knowledge. This indicates that students do not have enough understanding to medicate themselves properly. Keywords: Behavior, High School Student, Knowledge Level, Medication, Self-Medication